PERHITUNGAN DAN PENYUSUNAN JURNAL PENCATATAN BIAYA PRODUKSI PADA PONDOK BAKSO LESTARI KOTA PALEMBANG - Syafitri, Twenty Mariza; Nurpratiwi, Tiara; Anggreni, Meilinda; Wahyuni, Sri; Carolina, Dessy (Jurusan Akuntansi Politeknik Negeri Sriwijaya Palembang, 2024)
The determination of cost of goods manufactured is crucial for MSMEs (Micro, Small, and Medium Enterprises) to set selling prices, manage costs, and calculate profit and loss. Pondok Bakso Lestari, an MSME in Palembang, still uses a simple estimation method in calculating the cost of goods manufactured due to a lack of understanding of factory overhead costs. This community service aims to provide an understanding of the importance of analyzing and calculating the Cost of Goods Manufactured for business sustainability. The method used is assistance and training on calculating the Cost of Goods Manufactured using explanation methods and direct examples. As a result, business owners understand the importance of calculating and determining the Cost of Goods Manufactured. After the training, business owners are able to calculate and prepare cost of production accounting journals independently. In conclusion, Pondok Bakso Lestari can determine more competitive and affordable selling prices after understanding the calculation of the Cost of Goods Manufactured, thereby attracting customer interest and encouraging business sustainability.